Sexuality - Jones, Amelia; Jones, Amelia; Alloula, Malek; Brown, Norman O.; Butler, Judith (London : Whitechapel Gallery, 2014)
Acconci, Vito ; assume vivid astro focus ; Athey Ron ; Benglis, Lynda ; Byrne, Gerard ; Chakravarthi, George ; Chicago, Judy ; Tutti, Cosey Fanni ; Delvoye, Wim ; Elmgreen & Dragset ; Emin, Tracey ; VALIE EXPORT ; Fraser, Andrea ; Gómez-Peña, Guillermo ; Gonzalez-Torres, Felix ; Gupta, Sunil ; Hammond, Harmony ; Kelly, Mary ; Kusama, Yayoi ; Volcano, Del LaGrace ; Legorreta (Cyclona), Robert ; McCarthy, Paul ; Maple, Sarah ; Neshat, Shirin ; O'Grady, Lorraine ; Ono, Yoko ; Opie, Catherine ;Orlan ; Ostojic, Tanja ; Pope.L, William ; Schapiro, Miriam ; Schneemann, Carolee ; Semmel, Joan ; Smith, Barbara ; Sprinkle, Annie ; Szapocznikow, Alina ; Davis, Vaginal ; Wilke, Hannah, Wojnarowicz, David
Formerly CIP.
boek
Keywords: Sex in art; Art, Modern -- 20th century; Art, Modern -- 21st century; Art -- Psychology; Art -- Philosophy